Property Business Digital Marketing Communication Strategy during the Covid-19 Pandemic at Kartika Residence - Yunita; Amri Dunan (Publisher Cv. Inara, 2021)
This research aims to find out the digital marketing communication strategy of the property business during the Covid-19 pandemic at Kartika Residence. The methods in this research use qualitative research using the theories Diffusion of Innovation and E-marketing. The analysis was conducted with the theory of Diffusion of Innovation and E-Marketing. The results showed that digital marketing communication in the Kartika Residence property business is a container in building branding on digital media and promoting products. E-marketing, although helpful as a sales support tool, but the sales process will be able to be done if consumers have visited the location. So that the use of digital marketing is only at the stage of branding, promotion, prospecting, and then follow up.